2013
DOI: 10.1159/000346231
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of MLC601 (NeuroAiD®), a Traditional Chinese Medicine, in Poststroke Recovery: A Systematic Review

Abstract: Background: Subsequent to a pooled analysis of 2 trials, several more studies have been published assessing the benefit of MLC601 in stroke patients. Hence, it is timely to conduct an updated meta-analysis to frame the interpretation of the results of an ongoing large multicenter, randomized, double-blind, placebo-controlled study. Therefore, we conducted a systematic review of the efficacy of MLC601 in improving the recovery of stroke patients. Methods: PubMed® and the Cochrane Library® databases were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 23 publications
4
32
0
Order By: Relevance
“…27 We updated the meta-analysis to include all CHIMES patients, and this showed an OR for good functional outcome at the end of study period of 1.25 (95% CI, 1.00-1.56; P=0.05) in favor of MLC601 (Figure 4). Because all the studies in the systematic review had nonacute strokes with onset-to-treatment windows of ≤1 week to 6 months, we explored the effect of time window by including only CHIMES patients who started treatment >48 hours from stroke onset.…”
Section: Discussionmentioning
confidence: 99%
“…27 We updated the meta-analysis to include all CHIMES patients, and this showed an OR for good functional outcome at the end of study period of 1.25 (95% CI, 1.00-1.56; P=0.05) in favor of MLC601 (Figure 4). Because all the studies in the systematic review had nonacute strokes with onset-to-treatment windows of ≤1 week to 6 months, we explored the effect of time window by including only CHIMES patients who started treatment >48 hours from stroke onset.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies, which assessed the benefit and safety of MLC601 in non-acute stroke patients using different clinical outcomes [7,8,9,10,11,12,13,14,15,16,]have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies on patients with nonacute stroke showed that MLC601 (NeuroAiD TM ) improved recovery with a good safety profile. 6 Because MLC601 has been reported to improve cerebral blood flow velocity in patients with subacute stroke 7 and potentially induce ischemic preconditioning by activating ATP-dependent potassium channels, 8 we hypothesized that MLC601 may have an effect on preventing occurrence of early vascular events within 3 months of stroke onset.…”
mentioning
confidence: 99%